Returns to Emergency Department, Observation, or Inpatient Care Within 30 Days After Hospitalization in 4 States, 2009 and 2010 Versus 2013 and 2014. Issue 5 (22nd November 2017) - Nuckols, Teryl K.; Fingar, Kathryn R.; Barrett, Marguerite L.; Martsolf, Grant; Steiner, Claudia A.; Stocks, Carol; Owens, Pamela L.
Abstract : BACKGROUND: Nationally, readmissions have declined for acute myocardial infarction (AMI) and heart failure (HF) and risen slightly for pneumonia, but less is known about returns to the hospital for observation stays and emergency department (ED) visits. OBJECTIVE: To describe trends in rates of 30‐day, all‐cause, unplanned returns to the hospital, including returns for observation stays and ED visits. DESIGN: By using Healthcare Cost and Utilization Project data, we compared 210, 007 index hospitalizations in 2009 and 2010 with 212, 833 matched hospitalizations in 2013 and 2014. SETTING: Two hundred and one hospitals in Georgia, Nebraska, South Carolina, and Tennessee. PATIENTS: Adults with private insurance, Medicaid, or no insurance and seniors with Medicare who were hospitalized for AMI, H F, and pneumonia. MEASUREMENTS: Thirty‐day hospital return rates for inpatient, observation, and ED visits. RESULTS: Return rates remained stable among adults with private insurance (15.1% vs 15.3%; P = .45) and declined modestly among seniors with Medicare (25.3% vs 25.0%; P = .04). Increases in observation and ED visits coincided with declines in readmissions (8.9% vs 8.2% for private insurance and 18.3% vs 16.9% for Medicare, both P ≤ .001). Return rates rose among patients with Medicaid (31.0% vs 32.1%; P = .04) and the uninsured (18.8% vs 20.1%; P = .004). Readmissions remained stable (18.7% for Medicaid and 9.5% for uninsured patients, both P > .75) while observation and ED visits increased. CONCLUSIONS: Total returns to the hospital are stable or rising, likely because of growth in observation and ED visits. Hospitalists' efforts to improve the quality and value of hospital care should consider observation and ED care.